2010
DOI: 10.1677/joe-10-0300
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intrathyroidal dehalogenation by iodide

Abstract: Iodide is a trace element and a key component of thyroid hormones (TH). The availability of this halogen is the ratelimiting step for TH synthesis; therefore, thyroidal iodide uptake and recycling during TH synthesis are of major importance in maintaining an adequate supply. In the rat, the thyroid gland co-expresses a distinctive pair of intrathyroidal deiodinating enzymes: the thyroid iodotyrosine dehalogenase (tDh) and the iodothyronine deiodinase type 1 (ID1). In the present work, we studied the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…There has been no difference in neither TSH concentration nor plasma thyroid hormone levels observed between treated and control groups, respectively; this may suggest that the thyroid function has not been affected by the repeated administration of iodide. These results are in accordance with other clinical and preclinical studies that reported no impact of iodide on the pituitary-thyroid axis activity [15,21,33,37,[39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There has been no difference in neither TSH concentration nor plasma thyroid hormone levels observed between treated and control groups, respectively; this may suggest that the thyroid function has not been affected by the repeated administration of iodide. These results are in accordance with other clinical and preclinical studies that reported no impact of iodide on the pituitary-thyroid axis activity [15,21,33,37,[39][40][41][42][43].…”
Section: Discussionsupporting
confidence: 93%
“…Wolff and Chaikoff demonstrated in 1948 that an excess of iodide in rats may transiently disrupt thyroid function, the well-known Wolff-Chaikoff effect is characterized by a decrease in and delayed iodide organification [18]. This affects many steps of thyroid hormone synthesis and secretion; such iodide entrance and organification, iodide efflux through the colloid, intra-thyroidal iodide pool regeneration, and thyroid hormones transport [19][20][21][22]. This effect could lead to a temporary variation in thyroid hormones level, which exerts a major impact on development, growth, and metabolism [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, these differences were no longer observed after 3 weeks of treatment (209). A state of hypothyroidism can be achieved faster if PTU or MMI are combined with 1% KClO 4 in the drinking water, a potent NIS inhibitor (210,211). However, their combination will also magnify the effect that these drugs have on water consumption.…”
Section: And Recommendation 20amentioning
confidence: 99%
“…Although the mechanism for the acute Wolff–Chaikoff effect remains incompletely understood, it has been hypothesized to be due to the generation of intrathyroidal iodolactones, iodoaldehydes, or iodolipids, which inhibit thyroid peroxidase activity [6,7]. Reduced intrathyroidal deiodinase activity induced by high concentrations of iodine may also contribute to decreased thyroid hormone synthesis [8]. …”
Section: Iodine Excessmentioning
confidence: 99%